In vitro decidualisation of human endometrial stromal cells is enhanced by seminal fluid extracellular vesicles. Issue 1 (29th January 2019) - Rodriguez‐Caro, Helena; Dragovic, Rebecca; Shen, Mengni; Dombi, Eszter; Mounce, Ginny; Field, Kate; Meadows, Jamie; Turner, Karen; Lunn, Daniel; Child, Tim; Southcombe, Jennifer Helen; Granne, Ingrid
ABSTRACT: Extracellular vesicles are highly abundant in seminal fluids and have a known role enhancing sperm function. Clinical pregnancy rates after IVF treatment are improved after female exposure to seminal fluid. Seminal fluid extracellular vesicles (SF‐EVs) are candidate enhancers, however, whether SF‐EVs interact with cells from the endometrium and modulate the implantation processes is unknown. Here, we investigated whether SF‐EVs interact with endometrial stromal cells (ESCs) and enhance decidualisation, a requisite for implantation. SF‐EVs, isolated from human seminal fluid ( n = 11) by ultracentrifugation, were characterised by nanoparticle tracking analysis and Western blotting, and purified using size exclusion chromatography. Non‐decidualised and decidualised primary ESCs ( n = 5) were then treated with SF‐EVs. Binding of bio‐maleimide‐labelled SF‐EVs was detected by flow cytometry and fluorescence microscopy. Prolactin and IGFBP‐1 protein levels in culture media were also analysed after single and multiple SF‐EV exposure. SF‐EVs size ranged from 50 to 300 nm, and they expressed exosomal markers (ALIX, SYNTENIN‐1, CD9 and CD81). SF‐EVs bound to non‐decidualised and decidualised ESCs at similar levels. ESCs prolactin secretion was increased after single ( p = 0.0044) and multiple ( p = 0.0021) SF‐EV exposure. No differences were found in IGFBP‐1 protein levels. In conclusion, SF‐EVs enhance in vitro ESC decidualisation and increase secretion of prolactin, an essential hormone in implantation. This elucidates a novel role of SF‐EVs on endometrial receptivity. Abbreviations: ECACC: European Collection of Authenticated Cell Cultures; ESCs: endometrial stromal cells; EVs: extracellular vesicles; FCS: foetal calf serum; HRP: horse‐radish peroxidase; IFNγ: interferon‐gamma; IGF: insulin‐like growth factor; IGFBP‐1: insulin‐like growth factor binding protein 1; IVF: in vitro fertilisation; MVB: multivesicular bodies; NTA: nanoparticle tracking analysis; PRLR −/− : homozygous prolactin receptor knockout; RT: room temperature; SF‐EVs: seminal fluid extracellular vesicles; STR: short tandem repeat; TGFβ: transforming growth factor β; uNK: uterine natural killer